The role of elective neck dissection in patients undergoing salvage laryngectomy. Issue 10 (28th September 2012) - Amit, Moran; Hilly, Ohad; Leider–Trejo, Leonor; Popovtzer, Aharon; Gutfeld, Orit; Shvero, Jacob; Fliss, Dan M.; Cohen, Jacob T.; Bachar, Gideon; Gil, Ziv
<x xml:space="preserve">Abstract</x> Background We investigated the risk of neck metastases in patients undergoing salvage total laryngectomy in association with previous radiotherapy. Methods The medical records of 42 patients (51 neck specimens) with clinical N0 classification who underwent salvage total laryngectomy in 2 cancer centers were reviewed. Fourteen patients had previous radiotherapy to the central neck and 28 to the central and lateral neck. Results Staging before salvage total laryngectomy was similar in both groups. The risk of neck metastases in the central and central/lateral radiation groups was 12% and 18%, respectively (p = .69). Subgroup analysis revealed that 4 of 8 patients initially presenting with clinically N+ had neck metastases before surgery, versus 2 of 26 for those with clinically N0 (p = .015; relative risk [RR] = 4.67). The risk or metastases in the contralateral neck was 0 of 9. Conclusion The risk of neck metastases in patients who undergo either central or central/lateral neck radiotherapy is similar. Elective neck dissection seems appropriate in patients undergoing SLR. © 2012 Wiley Periodicals, Inc. Head Neck 35: 1392–1396, 2013